Science and technology education and future human needs - Lewis, J. L. (John L.); Kelly, P. J. (Science and technology education and future human needs, 1987)
Science and Technology Education and Future Human Needs is a collection of papers that tackle concerns in the education of future scientists, particularly concerns in identifying techniques and resource material.